Air exchange in urban canyons with variable building width: a numerical LES approach. (22nd August 2019) - Garau, Michela; Badas, Maria Grazia; Ferrari, Simone; Seoni, Alessandro; Querzoli, Giorgio
The aim of this work is to gain further insight into the role played by the building aspect ratio ( ARB, i.e., the ratio of the building width, WB, to the building height, H ) and its influence on street canyon flow. We carried out a series of large eddy simulations with arrays of obstacles with different widths, ranging from 0.5 to 2.0, and two canyon aspect ratios ( ARC, i.e., the ratio of the canyon width, W, to H ) ARC = 0.5 and ARC = 1.0. Experimental data was obtained in a water channel for the corresponding configuration and used to validate numerical simulations. Results were found strongly dependent on the building aspect ratios, with two distinct behaviours identified with respect to the canyon aspect ratio. The residence time decreases with decreasing ARB, irrespective of the canyon aspect ratio, suggesting that ARB and ARC can be optimised to guarantee optimal street canyon ventilation in urban planning.